MARKET STRUCTURE AND CONDCT OF COWPEA (Vigna unguiculata L.) MARKETING IN YOBE STATE, NIGERIA - Abdulhamid, H.; Gamawa, A. I.; Badejo, B. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed market structure and conduct of cowpea (Vigna unguiculata L.) Marketing in Yobe State Nigeria. Cowpea provides essential plant proteins, vitamins, and revenue for farming families however, market structure and conduct of cowpea have not been properly describe. The aim of the study was to described market structure and conduct of cowpea marketers in the study area. Primary data were collected with the aid of questionnaires. Using multistage sampling techniques, the data were collected from 142 producers-wholesalers, 144 wholesalers, and 182 retailers. The data were analysed using descriptive statistics and Herfindahl-Hirschman Index (HHI). The results indicated that; 98.59% of producers- wholesalers, 97.22% of wholesaler and 100% of retailers indicated that there were no restrictions on new players joining the market. However, Producers-wholesalers had HHI of 105.74, wholesalers had HHI of 149.20 and retailers had HHI of 83.18 indicating highly competitive market structure. Moreover, 91.55% producers-wholesalers, 93.75% of wholesalers and 68.68% of retailers revealed that they negotiated to determine the price of their cowpea products indicating market price is determine by demand and supply of the cowpea product. Most of the respondents were members of marketers’ association indicating marketers assist them through market information sharing. Market structures are perfectly competitive due to respondents’ absence of market dominance and misuse of market power in the study area. Further marketing studies on other crops needs to be carried out, taking into account producers-wholesalers as an additional marketing player in the marketplace.